Réponses

2013-03-24T18:09:22+01:00

1. 

E = (2x - 3)² - 16

E = 4x² - 12x + 9 - 16

E = 4x² - 12x - 7

 

2. 

E = (2x - 3)² - 16

E = (2x - 3 - 4)(2x - 3 + 4)

E = (2x - 7)(2x + 1)

 

3. Si x = 0 alors :

E = (2x - 7)(2x + 1) 

E = (2*0 - 7)(2*0 + 1)

E = - 7 * 1

E = -7

 

4.

(2x - 7)(2x + 1) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc :

2x - 7 = 0

2x - 7 + 7 = 0 + 7

2x / 2 = 7 / 2

x = 3,5

 

OU 

2x + 1 = 0

2x + 1 - 1 = 0 - 1

2x / 2 = -1 / 2

x = - 0,5